COMPOSITE PACKAGING AND THE ROLE OF ECO-DESIGN IN THEIR RECYCLING (Innovation in Woodworking Industry and Engineering design, 2026)
The beginning of composite packaging was laid in 1930, when ordinary paper rubbed with paraffin was used for packaging liquid and other “wet” products. According to the modern understanding of “composite packaging”, it is made of different materials that cannot be separated manually and none of them represents more than 95% of the weight of the package. Since composite packaging consists of many different materials, it cannot be recycled directly without being separated, which creates several difficulties and often leads to landfilling or incineration. In this regard, to improve the possibility of implementing a circular economy for composite packaging waste, innovative solutions are required for the separation and recovery of recyclable materials, but above all innovations in their design and ecodesign, which would facilitate their subsequent treatment and recycling.